Oxidized Lipoproteins Suppress Nitric Oxide Synthase in Macrophages: Study of Glucocorticoid Receptor Involvement - K. E. Matthys; P. G. Jorens; B. Marescau; M. Rosseneu; H. Bult; A. G. Herman (Mediators of Inflammation)
Activated cholesterol-laden macrophages in atherosclerotic lesions are believed to influence the progression of this disease. The induction of nitric oxide synthase (iNOS) activity was investigated in control and cholesterol-laden J774 macrophages, obtained by pre-incubation with oxidized or acetylated low density lipoproteins (oxLDL, acLDL). Loading with oxLDL caused a small induction of NOS activity in unstimulated cells, as indicated by nitrite and citrulline accumulation in the supernatant. However, it suppressed the iNOS activity resulting from stimulation of the cells with lipopolysaccharide with or without interferon-γ. AcLDL had no inhibitory effect, indicating that cholesterol accumulation as such was not responsible. Since the induction of NOS in macrophages is inhibited by glucocorticoids, the possibility that a glucocorticoid-like factor, formed during oxidation of LDL, may cause the inhibition, was investigated. However, addition of the glucocorticoid receptor antagonist mifepristone did not prevent the oxLDL-dependent NOS inhibition, indicating that the glucocorticoid receptor is not involved in the suppressive effect of oxLDL.